GAB (Generasi Anti Bullying) : Edukasi Anti Bullying Anak-anak di Desa Mojowono - Adil Abdillah; Witanti Rokmatulillah; Ahmat Rian Hanafi; Shinta Wahyu’aunillah; Novel Septianis Avanti; Firman Saifudin; Octia Manda Tasya; Fifit Nur Aini; Ilmia Putri Hariyono; Adhimas Arya H.A.P; Sayidatina Khaf Sho; Riki Hidayat; Septi Wulandari; Dwi Prasetyo Aji Agustin; Putri Ziana Walidah; Yuki Andri Okta Setiawan; Muamar Hendik Safri; Yogi Indra Devi; King Gusthi Marga Anthonie; Mentrik Hesti Maszaroh; La Rose Octaffina; Sherlina Aprilya; Zidnii Ilma (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
Bullying is an act of oppression that is carried out intentionally and repeatedly with the aim of hurting another person. Bullying can occur physically, verbally, or in subtle ways such as forcing or manipulating. Bullying can have a negative impact on victims, perpetrators and witnesses. Victims can experience psychological stress, behavioral changes and trauma. There are several reasons why someone does bullying, namely because they see their parents often fighting. Unhealthy parenting patterns, too liberated, too harsh, or lacking love and attention. This community service activity aims to provide education regarding the negative impacts of bullying and maintain the mental health of children in Mojowono village, Kemlagi subdistrict, Mojokerto regency. The target of this community service activity is 111 elementary school children from grades 1 to 6 using the hybrid learning method. The results of the evaluation of children's understanding of the material showed that 85% of children really understood the material presented